Systematicity of students' independent work in cloud learning environment - Oleksandr H. Kolgatin; Larisa S. Kolgatina; Nadiia S. Ponomareva; Ekaterina O. Shmeltser (Academy of Cognitive and Natural Sciences, 2019)
The paper deals with the problem of out-of-class students' independent work in information and communication learning environment based on cloud technologies. Results of appropriate survey among students of pedagogical university are discussed. The students answered the questions about systematicity of their learning activity and propositions for its improving. It is determined that the leading problems are needs in more careful instruction according to features of the task completing, insufficient experience in self-management, the lack of internal motivation. Most of all, students recommend to provide the tasks with detail instruction (oral or written) and to pay attention to careful planning the time that is necessary for full completion of the task. It is pointed that such complicated requirements can be satisfied only by complex use of information and communication technologies as well as the automated system of pedagogical diagnostics. Some requirements for management of students' out-of-classroom independent work are formulated as a result of this discussion.